Reviewing Two Decades of Value Creation in Tourism: An Attempt to Develop a Conceptual Framework - El Boukhari, Abdelouahab; Oumlil, Rachid; Achaba, Allal (Téoros)

(untitled) (Université du Québec à Montréal, 2020)
Tourism is one of the world economy pillars. In the last decades, it underwent an evolution related to consumer behaviour and technological progress. Facing this evolution, several efforts were made by companies; for example, some of them looked for new ways to create value. Despite a great number of studies conducted, the literature shows less evidence related to the variables that affect value creation in tourism companies. Hence, the objective of this paper is to propose a conceptual framework of value creation measurement in tourism through mapping the most frequent indicators in literature. To do so, the authors asked the following research question: what indicators of value creation in tourism were the most mobilized during the last twenty years? Then they performed a meta-analysis based on value creation papers published during the period ranging from 1997 to 2017. Furthermore, based on the NVivo 11 coding method, they processed 747 indicators, of which they considered that 66 were more frequently used as they had been cited at least twice. The main ones are service quality, customer satisfaction, environmental management, and profitability. They grouped these frequent indicators in five categories, namely: customers (10), employees and skills improvement (9), environment and natural resources (6), finance (20), and internal processes (21).